Constraint and Nonlinearization of Supersymmetric Equations with Some Special Forms of Lax Pairs - Hongmin Li (Advances in Mathematical Physics, 2020)
We study the null boundary problems of some classical evolution equations constrained by some special forms of Lax pairs. Furthermore, we present the constraint and nonlinearization of some supersymmetric (SUSY) equations with a special form of Lax pairs and solve the null boundary problems of these SUSY equations under the corresponding constraints.